A JOURNEY THROUGH SEXUAL VIOLENCE AGAINST CHILDREN AND ADOLESCENTS - Silva de Carvalho, Elaine (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The research proposes to take a reflective journey on the impacts of sexual violence against children and adolescents and the characteristics of this type of extreme violation of rights that in many cases generate irreparable and insurmountable impacts for the victims. The methodology was based on a qualitative and explanatory approach, the data collection was carried out through a bibliographical survey in order to build a trajectory on the context and characterizations of sexual violence from a broader perspective. This is important research from the point of view that it can be a guiding tool for professionals who work with services offered to the target audience and so that people who read it can orient themselves on the topic. It is unacceptable that this type of violence is still on the rise despite all the work to remedy this type of crime, which at its peak has led many children and adolescents to serious mental health problems and even self-extermination.
Keywords: sexual violence, children, adolescents